An Unbiased Appraisal of Purchasing Power Parity - McDermott, C. (IMF Working Papers; Working Paper ;, 2001)
Univariate studies of the hypothesis of unit roots in real exchange rates have yielded consensus point estimates of the half-life of deviations from purchasing power parity of between three to five years. However, least squares-based estimates of half-lives are biased downward. Accordingly, we follow Andrews (1993) and use median-unbiased estimators of the half-life of deviations from parity as a preferred measure of the persistence of real exchange rate shocks. We study this issue using real effective exchange rate (REER) data for 22 industrial countries in the post-Bretton Woods period. Three methods of bias correction are implemented, which yield cross-country averages of half-lives of deviations from parity ranging between 4 to 15 years, with the REER of several countries displaying permanent deviations from parity.